2015
DOI: 10.1080/09291016.2015.1052649
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin modifies scrotal circumference but not plasma testosterone concentrations and semen quality of rams during the seasonal anestrus at 43°S

Abstract: The effect of melatonin implants on semen quality in fresh and frozen/thawed semen, Scrotal circumference and plasma testosterone levels has been studied During two consecutive years in the Patagonia region of Argentina (43ºS). Sixteen Dohne Merino rams (experiment 1) and 12 Dohne Merino and Merino rams (experiment 2) were used from September to December 2011 and 2012, respectively. Half of the rams were treated with melatonin implants (M groups), the remaining rams being the non-treated, control group (C grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Previous studies of melatonin application in bucks and rams during the non‐breeding season have reported contradictory results, with some studies reporting that melatonin showed no effects, and others reporting positive effects with minor improvements to specific semen characteristics (Buffoni et al., ; Fazli‐Nezad et al., ; Kaya et al., ; Ramadan et al., ). Fatoba and Adeloye () reported a positive effect of exogenous melatonin on all characteristics of spermatozoa in bucks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies of melatonin application in bucks and rams during the non‐breeding season have reported contradictory results, with some studies reporting that melatonin showed no effects, and others reporting positive effects with minor improvements to specific semen characteristics (Buffoni et al., ; Fazli‐Nezad et al., ; Kaya et al., ; Ramadan et al., ). Fatoba and Adeloye () reported a positive effect of exogenous melatonin on all characteristics of spermatozoa in bucks.…”
Section: Discussionsupporting
confidence: 89%
“…In rams, exogenous melatonin implants had a positive effect on semen quality (increased motility of spermatozoa and testosterone levels) when applied in the non‐breeding season, whereas such effects were not demonstrated during the breeding season (Kaya et al., ). Some studies found that melatonin implants had no effect on semen quality in rams, regardless of season (Buffoni et al., ; Rosa, Silva, & Bryant, ). More recently, Fazli‐Nezad, Mamoeii, Kheradmand, and Sookhtezary () showed only positive effects of melatonin in rams in the non‐breeding season, with an increase of testicular circumference and volume and concentration of spermatozoa in ejaculates, but not on other semen quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Although beneficial effects of exogenous MT on endocrinological profiles and antioxidant profiles were reported in different livestock species (sheep: Buffoni et al 2015, cattle: Aggarwal et al 2005, goat: Jiménez et al 2014, buffalo: Ramadan et al 2019, mithun: Perumal et al 2018, similar line of studies were lacking in anestrus buffalo cows in tropical island ecosystem during summer season in Andaman and Nicobar Islands. MT release from the implant is continuous and does not follow the diurnal rhythm of endogenous MT secretion (Perumal et al 2018).…”
Section: Resultsmentioning
confidence: 98%
“…Melatonin has higher potency than Vit-E (Pieri et al 1994) and GSH/mannitol (Hardeland et al 1993) in removing the peroxyl radicals and in scavenging of hydroxyl radicals, respectively. Though, earlier studies pointed out that exogenous MT significantly improved the endocrinological profiles, fertility profiles in different species (sheep: Buffoni et al 2015, cattle: Aggarwal et al 2005, goat: Jiménez et al 2014, buffalo: Ramadan et al 2019, mithun: Perumal et al 2018; perusal of available literature revealed no information on hematological, biochemical, endocrinological, antioxidant and oxidative profiles in post partum anestrus Andaman local buffaloes during summer season in island ecosystem of Andaman and Nicobar Islands. Therefore, the present study was designed to assess the effect of exogenous slow release MT implantation in hematological, biochemical, endocrinological profiles, antioxidant and oxidative stress profiles in post-partum anestrous Andaman local buffalo cows during summer season in tropical humid island ecosystem.…”
mentioning
confidence: 97%
“…There is thus considerable ambiguity surrounding the practice of collecting semen for artificial insemination during the non-breeding season, as despite negative perceptions, it is unclear if sperm function is truly reduced during this period. Furthermore, though it appears evident that ram testicular function is able to be improved utilising slow-release melatonin implants [8,[15][16][17], thereby increasing sperm production, there are conflicting reports regarding whether melatonin exposure is able to seasonally modulate sperm functionality [8,16,18,19]. Regardless of whether reproductive upregulation in the ram occurs naturally or is artificially stimulated, spermatozoa are exposed throughout the spermatogenic cycle to the different endocrine conditions stimulated by melatonin, such as upregulated testosterone production at both a systemic and a testicular level [15,20], as well as to melatonin itself.…”
Section: Introductionmentioning
confidence: 99%